The U.S. Travel Health Pharmacists' Role in a Post-COVID-19 Pandemic Era - Keri Hurley-Kim; Karina Babish; Eva Chen; Alexis Diaz; Nathan Hahn; Derek Evans; Sheila M. Seed; Karl M. Hess (MDPI AG, 2022)
Background: Many countries have enforced strict regulations on travel since the emergence of the SARS-CoV-2 (COVID-19) pandemic in December 2019. However, with the development of several vaccines and tests to help identify it, international travel has mostly resumed in the United States (US). Community pharmacists have long been highly accessible to the public and are capable of providing travel health services and are in an optimal position to provide COVID-19 patient care services to those who are now starting to travel again. Objectives: (1) To discuss how the COVID-19 pandemic has changed the practice of travel health and pharmacist provided travel health services in the US and (2) to discuss the incorporation COVID-19 prevention measures, as well as telehealth and other technologies, into travel health care services. Methods: A literature review was undertaken utilizing the following search engines and internet websites: PubMed, Google Scholar, Centers for Disease Control Prevention (CDC), World Health Organization (WHO), and the United States Department of Health and Human Services to identify published articles on pharmacist and pharmacy-based travel health services and patient care in the US during the COVID-19 pandemic. Results: The COVID-19 pandemic has changed many country's entry requirements which may now include COVID-19 vaccination, testing, and/or masking requirements in country. Telehealth and other technological advancements may further aid the practice of travel health by increasing patient access to care. Conclusions: Community pharmacists should consider incorporating COVID-19 vaccination and testing services in their travel health practices in order to meet country-specific COVID-19 entry requirements. Further, pharmacists should consider utilizing telehealth and other technologies to increase access to care while further limiting the potential spread and impact of COVID-19.